Low intrapatient variability of histomorphological findings in periprosthetic tissues from revised metal/ceramic on polyethylene joint arthroplasties. Issue 5 (16th October 2017) - Vaculova, Jana; Gallo, Jiri; Hurnik, Pavel; Motyka, Oldrich; Goodman, Stuart B.; Dvorackova, Jana
Abstract: The type of tissue response to implant by‐products can be determined by examination of periprosthetic tissues. However, little is known about the most suitable location for tissue sampling. The main goal of this study was to evaluate the extent of variability in tissue response in relation to location of tissue sampling, implant fixation, age and sex in total joint arthroplasties with metal‐on‐polyethylene or ceramic‐on‐polyethylene bearing pairs. We processed 236 histology slides from 21 patients and focused on the association between the location of tissue samples and histological features. The presence of the synovial hyperplasia showed a significant association with the particular sampling site. A higher density of high endothelial cell venules was seen in the samples from around the joint, and polyethylene particles were more abundant in noncemented TJA but both findings did not show statistically significant association with the sampling site. The results showed a relatively small variance in the tissue response to prosthetic by‐products among tissues sampled from the same patient. Our findings indicate that tissue samples retrieved from similar distance from around the TJA during the revision operation show comparable results of histological analysis. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 2008–2018, 2018.